The Relationship among Job Satisfaction, Organizational Commitment and Employees’ Turnover at Unilever Corporation in Nigeria - Chiedu, Chiemeke Kingsley; Long, Choi Sang; Ashar, Hapriza BT (European Journal of Multidisciplinary Studies, 2022)
Employee turnover has become a key performance indicator for many organizations as they struggle to retain talented employees. The negative impact of turnover on organizational performance has continually forced organizational leaders to seek better ways of retaining valuable employees. The relationship between man and work has always attracted the attention of philosophers. A major part of men’s life is spent at work. Work is social reality and social expectation to which men seem to conform. It not only provides status to the individual but also binds him to the society. An employee who is satisfied with his job would perform his duties well and be committed to his job, and subsequently to his organization. This paper examines relationship among job satisfaction, organizational commitment and employees’ turnover intentions at Unilever Corporation in Nigeria. The data for this study was collected from 117 employees currently working at Unilever Nigeria PLC using the survey method via the questionnaire. Pearson Correlation and the multiple regression analysis techniques using the SPSS version 22.0 was used for the data analysis. The findings of the study revealed that both job satisfaction and organizational commitment have significant negative relationship with employee turnover intentions. In addition, organizational commitment was revealed to have a more dominant influence on employee turnover intentions than job satisfaction. Based on these findings, the implications, recommendations, practice, and theory were discussed.
Keywords: Relationship, job satisfaction, Organizational commitments, Employees Turnover, Unilever Nigeria